The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1161/circulationaha.110.947341
|View full text |Cite
|
Sign up to set email alerts
|

Survival Comparison of the Ross Procedure and Mechanical Valve Replacement With Optimal Self-Management Anticoagulation Therapy

Abstract: Background-It is suggested that in young adults the Ross procedure results in better late patient survival compared with mechanical prosthesis implantation. We performed a propensity score-matched study that assessed late survival in young adult patients after a Ross procedure versus that after mechanical aortic valve replacement with optimal self-management anticoagulation therapy. Methods and Results-We selected 918 Ross patients and 406 mechanical valve patients 18 to 60 years of age without dissection, ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 31 publications
1
64
0
Order By: Relevance
“…In a propensity-matched cohort study with a mean follow-up of 5.7 years, Mokhles et al 15 reported equivalent survival between the Ross procedure and mechanical AVR. Our data suggest that although overall survival is equivalent up to 20 years after surgery, patients undergoing mechanical AVR experience an excess of cardiac-and valve-related mortality, most of which occurs after 15 years.…”
Section: Long-term Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…In a propensity-matched cohort study with a mean follow-up of 5.7 years, Mokhles et al 15 reported equivalent survival between the Ross procedure and mechanical AVR. Our data suggest that although overall survival is equivalent up to 20 years after surgery, patients undergoing mechanical AVR experience an excess of cardiac-and valve-related mortality, most of which occurs after 15 years.…”
Section: Long-term Survivalmentioning
confidence: 99%
“…Several recent studies have shown that the Ross procedure may confer long-term survival equivalent to that of the age-and sex-matched general population. 6-10 Despite these excellent long-term outcomes, the Ross procedure has been the object of much criticism because of the complexity of surgical implantation, the exposure to a broad spectrum of complex reoperations, and the notion of transforming a single-valve disease into a double-valve disease.11,12 As a result, the routine use of this procedure has not gained widespread adoption and is limited to a few centers worldwide.There is a paucity of data comparing outcomes between the Ross procedure and mechanical AVR in young and middle-aged adults, [13][14][15][16] and no longitudinal study comparing long-term (≥20 years) outcomes between these 2 techniques has been published. Furthermore, a randomized trial is unlikely to be feasible because most surgeons and patients have a clear preference for a particular approach in this population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With the use of propensity score matching, late survival was compared between the two groups. 37 In comparable patients, there was no late survival difference in the first postoperative decade between the Ross procedure and mechanical aortic valve implantation with optimal anticoagulation self-management. The authors demonstrated that survival in these selected young adult patients was excellent, perhaps as a result of highly specialised anticoagulation selfmanagement, better timing of surgery and improved patient selection in recent years.…”
Section: Surgerymentioning
confidence: 89%
“…These findings are important, but may have been predicted from other comparative studies that also show similar survival of patients with Ross procedure versus mechanical AVR. 4 The increased hazard of thromboembolism and bleeding from systemic anticoagulation with warfarin are well-known complications of mechanical prostheses. So, what is unique in the report and how should clinicians use the comparative data?…”
mentioning
confidence: 99%